Béâtrice Picon-Vallin. Le Théâtre du Soleil: The First Fifty-five Years. Translated by Judith G. Miller. Routledge, 2021. - Deborah Gaensbauer (Studies in 20th & 21st Century Literature, 2021)
Review of Béâtrice Picon-Vallin. Le Théâtre du Soleil: The First Fifty-five Years. Translated by Judith G. Miller. Routledge, 2021. xi + 453 pp.
Keywords: Contemporary French Theater; Collaborative Theater; Ariane Mnouchkine; Hélène Cixous; Robert Lepage; Jean-Jacques Lemêtre